2022
DOI: 10.1177/14791641221129877
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial mitophagy protection combining rivaroxaban and aspirin in high glucose-exposed human coronary artery endothelial cell. An in vitro study

Abstract: Purpose Combination of Rivaroxaban plus Aspirin improved cardiovascular outcome in patients with stable cardiovascular disease. The aim was to determine if Rivaroxaban and acetylsalicylic acid alone or in combination may protect mitochondrial mitophagy in human coronary artery endothelial cells (HCAEC) exposed to D-glucose. Methods HCAEC were incubated under different conditions: 5 mmol/L glucose D-glucose (control), 30 mmol/L D-Glucose with and without 50 nmol/L Rivaroxaban (Rivaroxaban), 0.33 mmol/L ASA (ASA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Following mitochondrial damage and dysfunction, mitophagy plays a pivotal role in maintaining endothelial homeostasis by eliminating damaged or dysfunctional mitochondria, which can decrease the release of mitochondrial mtDAMPs and ROS to the cytoplasm from damaged or dysfunctional mitochondria, and attenuating endothelial disorder ( Figure 3 ) (Y. Chen Y et al, 2022 ; Zekri-Nechar et al, 2022 ; Zhang et al, 2008 ). Mitochondrial dysfunction induced by atherosclerosis-related risk factors in ECs is an important mechanism of atherosclerotic initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following mitochondrial damage and dysfunction, mitophagy plays a pivotal role in maintaining endothelial homeostasis by eliminating damaged or dysfunctional mitochondria, which can decrease the release of mitochondrial mtDAMPs and ROS to the cytoplasm from damaged or dysfunctional mitochondria, and attenuating endothelial disorder ( Figure 3 ) (Y. Chen Y et al, 2022 ; Zekri-Nechar et al, 2022 ; Zhang et al, 2008 ). Mitochondrial dysfunction induced by atherosclerosis-related risk factors in ECs is an important mechanism of atherosclerotic initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Following mitochondria damage, mitophagy removes damaged and dysfunctional mitochondria to maintain intracellular homeostasis in the cardiovascular system (Y. Chen Y et al, 2022 ; He et al, 2019 ; Huynh and Heo, 2021 ; Tu et al, 2022 ; Yang et al, 2022 ).Mitophagy-mediated elimination of damaged mitochondria alleviates mitochondrial damaged-induced EC injury or dysfunction ( Bhogal et al, 2018 ; Zekri-Nechar et al, 2022 ).…”
Section: Endothelial Mitophagy and Atherosclerosismentioning
confidence: 99%
“…Interestingly, co-administration of rivaroxaban enhanced the effect of aspirin. These findings show that rivaroxaban and aspirin combined can potentially support the endothelium from hyperglycemic conditions due to mitochondrial mitophagy protection (Zekri-Nechar et al, 2022a). Wu et al (2015) by using in vivo and in vitro models of diabetes aimed to examine the impact of rivaroxaban in angiogenesis.…”
Section: Rivaroxabanmentioning
confidence: 94%
“…Most studies have demonstrated that PINK1 and Parkin are downregulated in ECs exposed to high glucose (HG) and/ or free fatty acids (FFAs), whereas one study has revealed that PINK1 and Parkin are upregulated in the aortic endothelium of obese and diabetic mice. [21][22][23][24] Given these discrepancies, the abovementioned results need further confirmation in cardiac microcirculation under diabetic stress. The import of PINK1 into the mitochondria is an initial step in PINK1-Parkin-dependent mitophagy, after L-carnitine through the inhibition of PARL detachment from PHB2.…”
Section: Introductionmentioning
confidence: 94%
“…However, only the PINK1‐Parkin axis‐dependent pathway has been preliminarily introduced into ECs in diabetes mellitus or hyperglycemia, and the results remain controversial. Most studies have demonstrated that PINK1 and Parkin are downregulated in ECs exposed to high glucose (HG) and/or free fatty acids (FFAs), whereas one study has revealed that PINK1 and Parkin are upregulated in the aortic endothelium of obese and diabetic mice 21–24 . Given these discrepancies, the abovementioned results need further confirmation in cardiac microcirculation under diabetic stress.…”
Section: Introductionmentioning
confidence: 98%